Diagnostic Utility Of Scrape Cytology In The Intraoperative Diagnosis Of Breast Lumps (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: Scrape cytology is a modification of imprint cytology in the rapid intraoperative diagnosis of tumors. There are many controversies in rapid diagnosis of surgically removed specimens and single completely reliable method has not yet been developed. The study is undertaken to evaluate the role of scrape cytology which does not require special setup in the diagnosis of intraoperative lesions of breast.OBJECTIVES : To perform scrape cytology of surgically operable breast masses and evaluate its accuracy in relation to histopathological diagnosis.MATERIALS AND METHODS : A total of 82 surgically resected specimens from breast were examined by scrape cytology before formalin fixation and compared with histopathological sections which were considered as gold standard.RESULTS : Total 82 cases were subjected to scrape cytology 78 cases was given cytological diagnosis . Among 78 cases 43 were benign 35 were malignant lesions in comparison with histopathology showing sensitivity,specificity and accuracy of 100%,82.86% and 92.31% respectively .Conclusion : Intraoperative scrape cytology is a good complement to histopathology in the diagnosis of cancer where frozen section facilities are often not available, since a rapid preliminary diagnosis may help in surgical management planning .